Energy analysis in dairies of the Argentina Pampa´s region. Part 2. Energy accounting - Gimenez, Gustavo Daniel; Novaira, Bruno Idelfonso; Marini, Pablo Roberto (Agronomía Mesoamericana, 2022)
Introduction. Agricultural activity is a user and producer of energy, which can be evaluated through energy analysis, which also relates concepts of physics, biochemistry, and biology. Objectives. To evaluate from an expanded energy approach, different commercial models of primary milk production. Materials and methods. The study was based on retrospective data from nine dairy farms in the Pampa´s Argentina Region, between July 2014 and June 2015. Four indicators were calculated: energy output (EE), energy input (IE), energy efficiency (EE/IE), and anergy (A). Results. The highest EE were based on net primary productivity, under high supplementation conditions. The average IE was 239.9 GJ/ha/year, a range in which the systems with medium stocking rates were aligned. Water (67 %) was the main contributor. The efficiency (EE/IE) showed marked variability, based on the IE; although the vegetal biomass was the main cause of EE fluctuation, since the contributions of milk and meat did not differ between systems. The remaining energy stock (storage) was not used within the system, nor did it contribute to the system through its export, so it was defined as a fraction without practical use (A). Conclusions. The energy analysis was a valid tool to evaluate the sustainability of the systems, it was applied in production models with different intensification strategies. When including vegetal biomass, the highest energy outputs (EE) were seen in models with high supplementation, but in the dairy subsystem taken individually, animal stocking rate was associated with higher EE (due to increased productivity) and higher IE, due to the increase of water consumption.